Lateral Collateral Ligament and Biceps Femoris Tendon Fixation with a Suture Anchor to the Tibial Metaphysis after Proximal Fibula En Bloc Resections Preserve Lateral Knee Stability - Buyukdogan, Kadir; Işık, Samet; Ayık, Gökhan; Tokgözoğlu, Mazhar; Ayvaz, Mehmet (The Journal of Knee Surgery, 2022)
This study aims to analyze the functional outcomes and lateral knee stability of patients who underwent lateral collateral ligament (LCL) and biceps femoris tendon reconstruction with suture anchors after proximal fibula en bloc resection for bone tumors. Patients who underwent proximal fibular en bloc resection between 2007 and 2018 were retrospectively viewed. Patients were invited to visit the clinic, and their functional scores were evaluated using the Musculoskeletal Tumor Society Scoring (MSTS) system. Lateral knee stability was evaluated by varus stress radiographs obtained at 20 degrees of flexion, and the range of motion (ROM) of the bilateral knee was assessed. Side-to-side differences were graded according to the International Knee Documentation Committee (IKDC) criteria and compared between types I and II resections. A total of 17 patients (4 males and 13 females) with a mean age of 31.1 ± 17.1 (range: 13–65) years at the time of surgery were available for radiological and clinical examination at a mean follow-up of 68.6 ± 36.4 (range: 22–124) months after surgery. In terms of ROM measurements, IKDC grades and side-to-side differences in both flexion and extension were not significantly different between the groups. On varus stress radiographs, lateral knee gapping was measured to be 0.93 ± 0.91 mm in type-I resections and 1.83 ± 0.45 mm in type-II resections, and statistically significant differences were detected among the groups (p = 0.039). When the values were graded according to IKDC criteria, none of the knees were classified as abnormal, and no difference was observed between the groups. Mean MSTS score of patients with type-I resections was significantly higher than those of patients with type-II resections (92.7 vs. 84.4%, p = 0.021). In the subscale analysis, a significant difference was observed in the support scores (type I = 94.5%, type II = 70%; p = 0.001). The reattachment of LCL and biceps femoris tendon to the tibial metaphysis with a suture anchor is a simple and effective method to prevent lateral knee instability after proximal fibula resections.
Keywords: proximal fibula tumor; lateral collateral ligament; suture anchor; en bloc resection